Corresponding Member of RAS Olga Ivanovna Urazova - S. A. Necrylov (Бюллетень сибирской медицины, 2017)
The biography of doctor of medical sciences, Professor of the Pathophysiology Department of Siberian State Medical University, Corresponding Member of Russian Academy of Sciences, has been prezented. The main directions of scientific educational and public activity of the scientist are shown.